Brainstem Hypoxia Contributes to the Development of Hypertension in the Spontaneously Hypertensive Rat. Issue 4 (April 2015) - Marina, Nephtali; Ang, Richard; Machhada, Asif; Kasymov, Vitaliy; Karagiannis, Anastassios; Hosford, Patrick S.; Mosienko, Valentina; Teschemacher, Anja G.; Vihko, Pirkko; Paton, Julian F. R.; Kasparov, Sergey; Gourine, Alexander V.
<x xml:space="preserve">Abstract</x> Systemic arterial hypertension has been previously suggested to develop as a compensatory condition when central nervous perfusion/oxygenation is compromised. Principal sympathoexcitatory C1 neurons of the rostral ventrolateral medulla oblongata (whose activation increases sympathetic drive and the arterial blood pressure) are highly sensitive to hypoxia, but the mechanisms of this O2 sensitivity remain unknown. Here, we investigated potential mechanisms linking brainstem hypoxia and high systemic arterial blood pressure in the spontaneously hypertensive rat. Brainstem parenchymal PO2 in the spontaneously hypertensive rat was found to be ≈15 mm Hg lower than in the normotensive Wistar rat at the same level of arterial oxygenation and systemic arterial blood pressure. Hypoxia-induced activation of rostral ventrolateral medulla oblongata neurons was suppressed in the presence of either an ATP receptor antagonist MRS2179 or a glycogenolysis inhibitor 1, 4-dideoxy-1, 4-imino-d-arabinitol, suggesting that sensitivity of these neurons to low PO2 is mediated by actions of extracellular ATP and lactate. Brainstem hypoxia triggers release of lactate and ATP which produce excitation of C1 neurons in vitro and increases sympathetic nerve activity and arterial blood pressure in vivo. Facilitated breakdown of extracellular ATP in the rostral ventrolateral medulla oblongata by virally-driven overexpression of a potent ectonucleotidase transmembrane prostatic acid phosphatase results in a significant reduction in the arterial blood pressure in the spontaneously hypertensive rats (but not in normotensive animals). These results suggest that in the spontaneously hypertensive rat, lower PO2 of brainstem parenchyma may be associated with higher levels of ambient ATP and L-lactate within the presympathetic circuits, leading to increased central sympathetic drive and concomitant sustained increases in systemic arterial blood pressure.